Cognitive, academic, executive and psychological functioning in children with spastic motor type cerebral palsy: Influence of extent, location, and laterality of brain lesions. (May 2022) - Laporta-Hoyos, Olga; Pannek, Kerstin; Pagnozzi, Alex M.; Whittingham, Koa; Wotherspoon, Jane; Benfer, Kath; Fiori, Simona; Ware, Robert S.; Boyd, Roslyn N.
Abstract: Purpose: To investigate, in spastic motor-type cerebral palsy, the association between 1) the location and extent of brain lesions and numerous psychological outcomes; 2) the laterality of brain lesions and performance of verbal-related cognitive functions. Methods: The semi-quantitative scale for MRI (sqMRI) was scored for 101 children with cerebral palsy. Non-verbal and verbal proxy intelligence quotients (IQ), word reading, spelling, numerical operations skills, executive functioning, and psychological adjustment were assessed. Relationships between global and regional sqMRI scores and clinical scores were examined. The best multivariable linear regression model for each outcome was identified using the Bayesian Information Criteria. Regional sqMRI scores, gross motor functioning, manual ability, and epilepsy status were considered for inclusion as covariables. Where sqMRI scores made statistically significant contributions to models of verbal-related functioning, data were reanalysed including these sqMRI scores' laterality index. Verbal-related outcomes were compared between participants with left-sided versus bilateral brain lesions. Results: Medial dorsal thalamus and parietal lobe lesions significantly accounted for poorer verbal proxy-IQ. Left-hemisphere lateralization of temporal lobe lesions was associated with poorer verbal proxy-IQ. Participants with bilateral lesions performed significantly better than those with unilateral left-sided lesions in verbal cognitive functions. Controlling for epilepsy diagnosis, participants with ventral posterior lateral thalamus lesions presented with better Behaviour Rating Inventory of Executive Function scores, although within the normal range. sqMRI scores were not significantly associated with some psychological outcomes or these only bordered on significance after accounting for relevant control variables. Conclusion: The laterality of early-life lesions influences the development of verbal-related cognitive functions. Highlights: Brain lesions were scored using semi-quantitative MRI scoring system. Influence of brain lesion, motor functioning, and epilepsy status on academic attainment is explored. Observable brain lesions are associated with cognitive functioning in spastic CP. Lesions lateralized to the right temporal lobe are associated with better verbal proxy IQ.